PENGEMBANGAN BAHAN AJAR EVALUASI PEMBELAJARAN UNTUK PENDIDIKAN GURU SEKOLAH DASAR UNIVERSITAS KUNINGAN - Heru Purnomo; Isnaini Wulandari (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
Learning Evaluation is one of the compulsory subjects that must be taken by students at PGSD FKIP Kuningan University in order to obtain assessment and evaluation skills. However, there is no teaching evaluation material for PGSD that explicitly discusses the elementary school learning evaluation process. The purpose of this study is to develop instructional evaluation teaching materials on PGSD learning evaluation courses which are expected to equip students to be applied in primary schools when they become teachers. This research method is a research and development study by taking the object of research at the Kuningan University PGSD students (UNIKU). The results of the validation of learning evaluation material experts obtained results with a total score of 74 of the 20 learning indicators assessed with a range of scores 1-5 for the assessment of development products, so that a score of 3.7 from all assessment indicators in the learning evaluation instrument can be said with GOOD category. The results of student responses to the feasibility of developing teaching materials obtained by 90.27% of students on the response Very good and good. Based on the results obtained from the response to the readability of the product development, it was obtained that the response of students was 93.65% in the Very Good and Good categories. Based on the categorization of the gain score analysis in the Hake calculation table, the value of 0.59 is categorized as Medium. Then it can be concluded that the Learning evaluation teaching materials for Kuningan University PGSD students can be declared eligible for use